Emplacement and the politics of heritage in low-income neighbourhoods of Marseille. Issue 2 (7th February 2016) - Ingram, Mark
Abstract : Recent scholarship addressing efforts to celebrate heritage in low-income neighbourhoods and housing estates has stressed the importance of attending to the continuity of place-based social relationships as a key factor in residents' understandings of heritage, and, drawing on Smith's conception of an 'authorised heritage discourse', the ways these understandings differ from hegemonic and generalised expert discourse emphasising the deficiencies of the material environment. In this article, I examine a new object of state intervention in France, 'the heritage of popular neighbourhoods', and describe points of convergence and conflict between local heritage work in Marseille and the recent discursive framework established to employ heritage as a tool in reorganising French state policy towards urban peripheral neighbourhoods (the politique de la ville). Drawing on ethnographic research (2007–2014), this article identifies emplacement as a key feature in residents' performances of neighbourhood heritage, a feature often absent or poorly elaborated in heritage work promoted by French urbanist policy in the past. I describe the ways emplacement has been expressed aesthetically in arts projects, trace the range of social networks and relationships enacted, and describe the political implications of these performances as a tool for promoting solidarity across time and space in Marseille.